Burden of non-communicable disease studies in Europe: a systematic review of data sources and methodological choices - Charalampous, Periklis (2022)
© The Author(s) 2022. Published by Oxford University Press on behalf of the European Public Health Association. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0/), which permits unrestricted reuse, distribution, and reproduction in any medium, provided the original work is properly cited.